Measuring Rural Access : Using New Technologies - World Bank Group (World Bank, Washington, DC, 2016)
Transport connectivity is an essential part of the enabling environment for inclusive and sustained growth. In many developing countries, particularly in Africa, the vast majority of farmers are still disconnected from local, regional, and global markets. To reduce poverty and support inclusive economic growth, rural access is key. The Sustainable Development Goals (SDGs) aim to build resilient infrastructure, promote inclusive and sustainable industrialization, and foster innovation(Goal 9), for whichTarget 9.1 is to develop quality, reliable, sustainable andresilient infrastructure…to support economic developmentand human well-being, with a focus on affordableand equitable access for all. The Rural Access Index (RAI)is proposed as an indicator to measure this target.The definition is also simple enough to understand and usenot only in transport, but also in the broader development context, such as poverty alleviation. In the initial study, the RAI was estimated at 68.3 percent based onhousehold surveys, leaving a rural population of about one billion unconnected to a good quality road network. It is important to update the RAI in a timely manner anduse it in actual operations. Unfortunately, however, the previous methodology has several disadvantages, suchas inconsistency across countries, lack of sustainability ofregular updates, and weak operational relevance and clientownership. In particular, it is generally costly to relyon a household survey, which limits the sustainability ofthe index. In addition, the household-based approachcannot be spatially representative enough, limiting operational usefulness. With different tools and innovative technologies, it is now becoming easier and very possible to collect data, update the condition of the road network, and revise the RAI more regularly.